Photo-elastic effect, thermal lensing and depolarization in a-cut tetragonal laser crystals. (6th May 2016) - Yumashev, K V; Zakharova, A N; Loiko, P A
Abstract: We report on analytical description of thermal lensing effect in tetragonal crystals cut along the [1 0 0] crystallographic axis, for the two principal light polarizations, E ┴ c and E || c, under diode-pumping (plane stress approximation). Within this approach, we take into account anisotropy of elastic, photo-elastic, thermal and optical properties of the material. Expressions for the 'generalized' thermo-optic coefficient χ are presented. It is shown that astigmatism of thermal lens is determined both by the photo-elastic and end-bulging effects. The sign of the photo-elastic term χ ″ can be either positive or negative affecting significantly the sign of the thermal lens. Depolarization loss in a-cut tetragonal crystals is few orders of magnitude lower than that in cubic crystals. Calculations are performed for a -cut tetragonal molybdates, Nd:CaMoO4, Nd:PbMoO4 and Nd:NaBi(MoO4 )2 .